Employment Perceptions of Parolees: The Role of Perceived Barriers and Criminal Thinking - Varghese, Femina P. (International journal of offender therapy and comparative criminology, 2021)
This study explored offenders’ perception of their barriers to employment and investigated the role of criminal attitudes in parolees recently released from prison. An analysis of open-ended responses from offenders indicated that they perceived having a criminal record as the largest barrier to employment. Structural equation modeling, utilizing a cross-sectional design, indicated moderate support for a model of criminal thinking as a predictor of perceived barriers and of self-efficacy. Survey results also found that criminal attitudes have a positive direct relationship with perception of barriers in work and education, with perception of barriers increasing as criminal thinking increases. Furthermore, criminal thinking has a negative direct relationship with job search self-efficacy, with job search self-efficacy decreasing as criminal thinking increases. Criminal thinking also had an indirect relationship with career aspirations through job search self-efficacy. Findings have implications for vocational programming for parolees.